2017
DOI: 10.1007/s10508-017-0971-z
|View full text |Cite
|
Sign up to set email alerts
|

The Symbolic Nature of Trust in Heterosexual Adolescent Romantic Relationships

Abstract: Trust contributes to young people's capacity for sustaining current and future successful relationships. To date, research has yet to examine the meaning of trust in early dating relationships and reasons for its deterioration. The present study focused on video-recorded conversations about trust between 34 heterosexual adolescent couples in dating relationships living in the U.S. Transcripts from these conversations were qualitatively analyzed using thematic analysis to identify adolescents' meanings of trust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The perceived acceptance of sexting within romantic relationships suggests that sexting is viewed as safer with a trusted partner. One of the core expectations of romantic relationships is trustworthiness (Norona et al, 2017), the belief that another person has an “intrinsic motivation to take one’s own best interest into account when acting” (Boon & Holmes, 1991, p. 88, in Norona et al, 2017). This argument is strengthened by peers being critical of sexting with someone unknown, which could increase the risk of spreading sexts and for sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The perceived acceptance of sexting within romantic relationships suggests that sexting is viewed as safer with a trusted partner. One of the core expectations of romantic relationships is trustworthiness (Norona et al, 2017), the belief that another person has an “intrinsic motivation to take one’s own best interest into account when acting” (Boon & Holmes, 1991, p. 88, in Norona et al, 2017). This argument is strengthened by peers being critical of sexting with someone unknown, which could increase the risk of spreading sexts and for sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The topic of trust appears to be central in the relationship experiences of adolescents. Using observational methods with couple dyads, Norona, Welsh, Olmstead, and Bliton () found that the lack of trust for a romantic partner was salient in their sample of adolescents. Lack of trust seemed to stem from participants lowered self‐esteem, past relationship experiences, and gossip among their peers.…”
Section: Romantic Relationships and Sexual Activity In Adolescence Anmentioning
confidence: 99%
“…Although perhaps more stable than adolescent relationships, young adults still experience relationship instability and frequently engage in serial monogamous relationships (Arnett, ). With the exception of a few studies (e.g., Norona et al, ), most of the studies reviewed focused on the individual as the unit of analysis and thus are subject to problems related to shared‐method variance. That is, the independent and dependent variables were measured using self‐report measures from the same individual.…”
Section: Research In the Next Decade And Beyondmentioning
confidence: 99%
“…Moreover, motivations for sex may be interchangeable within a given dyad over the course of days, weeks, months, and years, with changes supported by trust and distrust experiences developing through repeated encounters, both sexual and nonsexual (Mullinax et al, 2016a). Specific sexual behaviors-first coitus or first receptive anal sex, for example-are used to signal trust and serve as "gifts" to the partner, in part to maintain the dyad relationship (Carpenter, 2002;Norona, Welsh, Olmstead, & Bliton, 2017).…”
Section: Role Of Trust In Sexual Interactionsmentioning
confidence: 99%